Prevalence and incidence of thyroid dysfunction in type 1 diabetes, type 2 diabetes and latent autoimmune diabetes of adults: The Fremantle Diabetes Study Phase II. (3rd February 2020) - Peters, Kirsten E.; Chubb, Stephen A. Paul; Bruce, David G.; Davis, Wendy A.; Davis, Timothy M. E.
Abstract: Objective: Since the results of published studies assessing thyroid dysfunction complicating diabetes have been variable in quality, inconsistent and may not reflect contemporary clinical care, the aim of this study was to determine its prevalence and incidence in a large, well‐characterized, representative cohort. Design: Community‐based, longitudinal, observational study. Patients: A total of 1617 participants from the Fremantle Diabetes Study Phase II (FDS2), including 130 (8.0%) with type 1 diabetes, 1408 (87.1%) with type 2 diabetes, and 79 (4.9%) with latent autoimmune diabetes of adults (LADA). Measurements: Serum thyrotropin (TSH) and free thyroxine (FT4) at baseline between 2008 and 2011 and in those attending Year 4 follow‐up. Results: The prevalence of known thyroid disease (ascertained from baseline self‐reported thyroid medication use or hospitalization data) was 11.7% (189/1617). Of the remaining 1428 participants, 5.1% (73/1428) had biochemical evidence of subclinical hypothyroidism, 1.1% (15/1428) overt hypothyroidism, 0.1% (2/1428) subclinical hyperthyroidism and 0.2% (3/1428) overt hyperthyroidism, representing an overall baseline prevalence of thyroid disease of 17.4% (282/1617). During 5694 patient‐years of follow‐up, 25 (3.0%) of the 844 with a normal baseline TSH and follow‐up data developed known thyroid disease. Of the remaining 819, 3.4% developed subclinical hypothyroidism, 0.2% overt hypothyroidism and 0.5% subclinical hyperthyroidism. There were no statistically significant differences in the prevalence or incidence of thyroid dysfunction by diabetes type. Conclusions: Thyroid dysfunction, known or detected through screening, is common in diabetes. These data suggest the need for periodic clinical and biochemical screening for thyroid disease in all types of diabetes.